Introduction: "Suffering Sappho!": Lesbian content and queer female characters in comics. Issue 4 (2nd October 2018) - Abate, Michelle Ann; Grice, Karly Marie; Stamper, Christine N.
ABSTRACT: Comics have been an important locus of queer female identity, community, and politics for generations. Whether taking the form of newspaper strips, comic books, or graphic novels and memoirs, the medium has a long history of featuring female same-sex attraction, relationships, and identity. This special issue explores the past place, current presence, and possible future status of lesbianism in comics. It features essays about cartoonists such as Jennifer Camper, characters such as Wonder Woman, and titles such as Lumberjanes . This special issue also includes a roundtable that examines underrepresented identities in lesbian comics. These pieces address subjects ranging from the depiction of a Latina lesbian protagonist in AMERICA: The Life and Times of America Chavez and the debut of the first lead Black lesbian female superheroine in Cyberzone to the presentation of queer women in graphic novels from South Asia and the experience of re-reading Hothead Paisan in the age of Trump.